PENGELOLAAN HUBUNGAN MASYARAKAT DALAM PENGEMBANGAN HUBUNGAN EDUKATIF - Bella Sukma, Adriana Hanny; Maryati, Mimin; Permana, Hinggil; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2025)
Public relations management is an important aspect in the world of education to strengthen the relationship between educational institutions and stakeholders. Through effective public relations management, educational institutions can build good educational relationships with students, teachers, parents, and the surrounding community. This research aims to explore public relations management in the development of educational relationships through library research method. The results of this study indicate that public relations management can be done through various strategies such as open communication, stakeholder participation, and the use of information technology. The results show that community relations management plays an important role in the sustainable development of educational relations. The role of the local government in community relations management is to coordinate the various parties involved in the development of educational relations and provide the necessary resources. The role of schools is to provide programs and activities that support the development of educational relations with the community. Meanwhile, the role of the community is to be part of the process of developing educational relations and supporting the programs organized. The conclusion of this study is that good community relations management can strengthen educational relations between schools and the community, as well as support the creation of an inclusive and sustainable learning environment.